Free radical scavenging activity of an aerial part of Aconitum heterophyllum (wall) from Kashmir Himalayas, India - Ayaz Ahmed; Ranjana Singh; Ravi Upadhyay (International Journal of Phytomedicine, 2015)
The plant Aconitum heterophyllum native to Kashmir has been widely used as a traditional medicine to cure diseases associated inflammations, cardiovascular, neurodegenerative and other ailments, microbial, bronchitis and joint pains since times. Keeping this in view the present study was carried out to investigate the antioxidant potential and the phytoconstituents composition of the plant extract. Various compounds were detected in the preliminary screening of the leaf extract of the plant, among them were the dominance of alkaloids and flavanoids. Wide range of antioxidant activity was detected in the plant compared to the standard antioxidants.